2023
DOI: 10.1002/dmrr.3655
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics, prebiotics, and synbiotics in type 1 diabetes mellitus: A systematic review and meta‐analysis of clinical trials

Abstract: Dysbiosis or imbalance of microbes in the gut has been associated with susceptibility and progression of type 1 diabetes mellitus (T1DM). The present systematic review and meta‐analysis examined the effects of probiotics, prebiotics, and synbiotics on fasting blood glucose (FBG), haemoglobin A1c (HbA1c), C‐peptide, and insulin requirements in T1DM patients. A systematic search for trials published up to October 2022 was conducted in PubMed, EMBASE, Scopus, Google Scholar, ScienceDirect, Web of Science, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…While the moderate heterogeneity aligned with the literature [20], the combined effect varied, which might be attributed to the differentiation between T1D and T2D. This review further demonstrated an improvement in DIU and FCP, contradicting the negative results from another review [19]. Furthermore, three studies conducted post-interventional biochemical examinations, revealing no significant difference between the MMA and control groups [15,34,37].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…While the moderate heterogeneity aligned with the literature [20], the combined effect varied, which might be attributed to the differentiation between T1D and T2D. This review further demonstrated an improvement in DIU and FCP, contradicting the negative results from another review [19]. Furthermore, three studies conducted post-interventional biochemical examinations, revealing no significant difference between the MMA and control groups [15,34,37].…”
Section: Discussionmentioning
confidence: 54%
“…Conversely, the literature specifically addressing T1D is notably limited, with only two existing reviews identified. One review, encompassing five randomized controlled trials (RCTs) up to 8 October 2022, examined the impact of probiotics and synbiotics on glycemic control, focusing on outcomes such as fasting blood glucose (FBG), HbA1c, fasting C-peptide (FCP), and daily insulin usage (DIU) [ 19 ]. However, it did not delve into the outcomes related to T1D pathogenesis, such as inflammatory cytokines and gut microbiota composition.…”
Section: Introductionmentioning
confidence: 99%
“…11 Finally, we have decided to include additional articles that do not necessarily relate to the topic of chrononutrition, but that we believe would still provide extremely important information in their related fields of dietetics, nutrition, and cardiometabolic diseases. These articles include discussions on the role of prebiotics, probiotics, and synbiotics, in patients with type 1 diabetes mellitus 12 the role of transitioning from a metabolically healthy obesity phenotype to a metabolically unhealthy obesity phenotypes on atherosclerotic risk and its related editorial written by experts in the field, 13,14 the role of pharmacologic and nutritional interventions in patients with post-bariatric surgery-related hypoglycaemia 15 and the effects of microbiome and nutraceutical in patients with type 2 diabetes. 16 In conclusion, this Special Issue will provide novel insights and clarifications on chrononutrition, but also on additional controversial topics.…”
Section: Special Issue: Chrononutrition and Other Nutrition Controver...mentioning
confidence: 99%
“…In secondary prevention, the use of probiotics/synbiotics was associated with reduction of pro-inflammatory cytokines (IL-1, IL-8, IL-17, MIP-1β, RANTES, and TNF-α), oxidative stress (hs-CRP), and an increase in total antioxidant capacity and the anti-inflammatory cytokine TGF-β1. Meta-analyses evaluating the effect of probiotics showed HbA1c and fasting blood glucose reduction [20][21][22].…”
Section: Environmental Interventionsmentioning
confidence: 99%